Assessment of Postnatal Depression Among Australian Lesbian Mothers - Khajehei, Marjan; Doherty-Poirier, Maryanne; Tilley, Peter (International Childbirth Education Association, 2012)
This cross-sectional study used a combination of three relative, reliable and standard questionnaires to evaluate symptoms of depression, sexual function and relationship satisfaction in the first year postpartum of sixteen lesbian mothers. The questionnaire was administered online. When individual scores were analyzed, there were 5 women who were depressed and 11 who were not. Those who were non-depressed had better sexual functioning and a higher level of satisfaction with relationships. This pilot study indicated that the need for further studies with lesbian mothers.